Imperforate hymen: the importance of early diagnosis - Enes, Pedro Vieira; Brandão, Pedro; Ramôa, Paula; Torgal, Ana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
The imperforate hymen is one of the most common obstructive lesions of the female genital system, with a prevalence from 1: 1000 to 1: 10000. Anomalies of the hymen are due to incomplete degeneration of the hymen central portion. It can be diagnosed at physical examination from birth and treated surgically. The most common clinical presentation is cyclic pelvic abdominal pain, urinary retention and hematocolpos. 12-year-old girl, premenarche who appealed to the Emergency department with abdominal pain and bilateral lumbar irradiation, over 2 weeks of evolution. Physical examination showed abdominal tumefaction in the hypogastric region, painful to palpation and under tension. Gynecological examination revealed an imperforate hymen, protruding from the introitus. Rectal ultrasonography performed at the emergency room showed vaginal distension with a hypoechoic content of 16 cm, larger diameter. Surgical hymenectomy was performed as treatment. On the 58th postoperative day, the patient was asymptomatic. The authors present a clinical case of imperforate hymen diagnosed at menarche, an anomaly diagnosed increasingly early due to the earlier physical examination that involves observation of the external genitalia of the new-born and the pre-pubertal child.